The development of gender conjugation in the Iranian verb (Atti del Sodalizio Glottologico Milanese, 2014)
This study illustrates the development of the gender agreement in verb conjugation, which can be reconstructed in some linguistic varieties of West Iranian family, from Old Persian to Modern Central Dialects and Southern Tāti. A widely accepted hypothesis towards the rise of gender conjugation claims that agreement markers on verb always arise from grammaticalization of anaphoric pronouns. Never the less, in the case we are dealing with, gender conjugation is based on the agreement of the past participle. KEYWORDS: verbal inflection, agreement, Iranian languages, gender conjugation, grammaticalization